Importance of hospital facilities management performance indicators: Building practitioners' perspectives. (January 2022) - Lai, Joseph H.K.; Hou, Huiying (Cynthia); Chiu, Betty W.Y.; Edwards, David; Yuen, P.L.; Sing, Michael; Wong, Philip
Abstract: Hospitals are critical infrastructure assets and the strategic management of facilities within these buildings are quintessentially important to society who rely upon effective healthcare services. Despite their importance to the optimised functioning of hospital facilities, standardized performance evaluation measures such as key performance indicators (KPIs) have hitherto received scant academic attention. Understanding the views of practitioners working on the different lifecycle stages of a building will help to establish pragmatic KPIs for hospital facilities management (FM). Hence, a multi-stage study was undertaken, within which interpretivism and inductive reasoning was utilised to conduct a systematic review of extant literature on hospital FM and KPIs. In parallel, the initial stage of work shortlisted 18 KPIs, in four categories (physical, safety, environmental and financial), as essential for hospital FM performance evaluation. Using these indicators, a questionnaire survey was developed and disseminated to building practitioners in the hospital sector of Hong Kong. Data gathered was then analysed using both summary and inferential statistics. The analyses reveal that the practitioners generally regarded the physical and financial indicators as more important. When compared between the perspectives of the design/construction practitioners and the FM group, significant differences were found with three particular KPIs: availability of fire services system, energy utilization index and carbon emissions per building area . The paper concludes with direction for future research that seeks to analytically determine the importance weighting of each performance indicator identified, which is requisite for establishing a credible hospital FM performance evaluation scheme. Highlights: A systematic review revealed limited research on hospital FM performance measures. Surveyed building practitioners' perceived importance of 18 hospital FM KPIs. The practitioners regarded the physical and financial KPIs as more important. Design/construction and FM practitioners perceived 3 of the 18 KPIs differently. Signpost future direction to determine importance weightings of the KPIs.